Warm nights disrupt transcriptome rhythms in field-grown rice panicles - Desai, Jigar S.; Lawas, Lovely Mae F.; Valente, Ashlee M.; Leman, Adam R.; Grinevich, Dmitry O.; Jagadish, Krishna S.V.; Doherty, Colleen J. (National Academy of Sciences, 2021)
SignificanceThe effects of warmer nighttime temperatures (WNT) on crops are one poorly understood dimension of climate change. WNT result from the asymmetrical increase in nighttime versus daytime temperatures. In rice, WNT reduce grain yield and quality. WNT reduce the amplitude of daily temperature cycles plants use to set their circadian clock. Therefore, we examined how WNT affect the timing of molecular activities. In field-grown plants, WNT alter the daily pattern of the transcriptome. Genes with strong rhythmic expression and those under circadian control are affected most by WNT. Many candidate regulators of the disrupted genes are circadian clock associated, emphasizing the altered timing under WNT. The pathways and mechanisms identified can assist efforts to identify lines tolerant to WNT.